Traces of the Heritage of Rantauprapat Kingdom (Oral History Review) - Suri Daehsan Purba; Hasan Asari; Nabila Yasmin (Yupa: Historical Studies Journal, 2023)
The Kingdom of Rantauprapat was a small kingdom that initially emerged in the upper reaches of the Bilah River. This research focuses on reconstructing the history of the Rantauprapat Kingdom through the utilization of historical relics found and historical research methods, as well as oral history methods. In particular literature, the starting point of the Rantauprapat kingdom is referred to as Poeldung. It is estimated that this kingdom existed from the late 18th century to the early 19th century, and it is known that the founder, named Patuan Bolatan, originated from Toba and was laid to rest behind the Sioldengan Village Castle housing. The existence of this kingdom became more evident during the reign of Patuan Bolatan's son, King Muda, around the mid-19th century. This was marked by the construction of the Palace in Sibuaya, formerly known as "Lobu in Bendahara Street," which has left a legacy as an ancient tomb complex. The existence of this kingdom subsequently extended from the king's residence on Padi Street to the relics of shop houses with ancient building typology on Pasar Lama Street and Veteran, as well as a tomb belonging to the last king of Rantauprapat, located in the Paindoan TPU complex